Carbon Credits: Effect on the Economy and Environment - Javed, Adnan Ahmad; Nauman, Muhammad Mustafa; Israr, Hamdan; Inam, Shaheer (Indonesian Journal Publisher, 2025)
This paper encompasses topics, including the implications of global warming, the intricacies of carbon markets, the benefits associated with carbon emissions reduction, and an evaluation of systems like net zero alongside other initiatives designed to normalize the discourse on carbon credits. Furthermore, it revisits and critically assesses previously established protocols and propositions within this sphere. It evaluates the practicality and efficiency of these methods and presents a conclusion. Moreover, the paper establishes connections with campaigns, introducing schemes, models, and mechanisms that have emerged in response to the growing concern over climate change. These integrations are presented as components that contribute to the impact of carbon credits on environmental governance and policy-making. By weaving together these elements, the paper aims to shed light on the role that carbon credits play in maintaining environmental sustainability, and underlining how crucial they are in the future of this field